The exposure about CSR Effect of CSR Disclosure on Survey Profitability of Food and Beverage Sub-Sector Companies on the Stock Exchange in 2019-2021 - Zaena, Rosye; Asyari (PT FORMOSA CENDEKIA GLOBAL, 2023)
CSR is a business commitment to contribute to sustainable economic development through collaboration with local communities and the general public to improve a decent life. The concept of CSR involves partnership responsibility between the government, community resource organizations and local (local) communities. This partnership is not static and passive. The purpose of this study was to determine the effect of CSR disclosure on profitability as measured by the variables ROA, ROE and EPS. The statistical method used in this research is inferential statistics, while the type of research used is descriptive verification research. The sample in this research is a manufacturing company in the food and beverage sector from 2019 to 2021. The sample used is a saturated sample. The analytical tool used in this study uses multiple regression analysis. The results showed that CSR disclosure had a significant effect of 52.6% on ROA, ROE and EPS